The effectiveness of Averrhoa bilimbi juice to improve peat water quality - Muhammad Iman Faisal Harahap; M. Hasbi; Budijono ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Averrhoa bilimbi juice contain s that can reduce organik matter, turbidity and color to improve peat water quality. A research aims to understand the effectiveness of A. bilimbi juice to improve peat quality water was conducted on May – October 2015. The method applied was RBD with 4 different concentration of A. bilimbi juice: P0 (0 mlL-1as control), P1 (30 mlL-1), P2 (35 mlL-1) and P3 (40 mlL-1) and different sampling time, first day (D1), second day (D2) and third day (D3). Parameter measured were turbidity, organik matter and color. These parameters were measure in the research showed that edition of Averrhoa bilimbi juice can reduce organik matter, color and turbidity. In the first day (D1) the best treatment was P3D1, as the turbidity reduced from 805 NTU to 34.9 NTU, organik matters from 1590.5 mg/L to 603.7 mg/L and color from 19010 PtCo to 1037 PtCo. In Second day (D2) the best treatment was P3D2, the turbidity reduced from 901.5 NTU to 33.5 NTU, organik matters from 1303 mg/L to 365.9 mg/L and color from 16.555 PtCo to 894 PtCo. In third day (D3) the best treatment was P2D3, the turbidity reduced from 855 NTU to 38.7 NTU, organik matters from 1135 mg/L to 231.4 mg/L and color from 23.400 PtCo to 669 PtCo. The highest survival rate of Cyprinus carpio and Oreochormis niloticus that were reared in the treated water for 4 days was in the P1 (70 %).Keyword: Peat water, Averrhoa bilimbi.